Supplementary Figure S1 from Dysregulation and Epigenetic Reprogramming of NRF2 Signaling Axis Promote Acquisition of Cisplatin Resistance and Metastasis in Head and Neck Squamous Cell Carcinoma - Abdullah A. Osman (15056323) (2025)
Cisplatin resistant HNSCC cells migrate faster than their Cisplatin sensitive counterparts.